Inhibitory activity of psilocybin/psilocin towards the enzymes of the cytochrome P450 (CYP450): an in vitro evaluation - Brito-da-Costa, A. M. (2023)
Background: Psilocybin is a hallucinogen produced by several “magic mushrooms” [1,2]. This prodrug is rapidly metabolized in the organism by alkaline phosphatases and esterases into psilocin, the active drug [1,2]. A scientific gap exists regarding the possible interactions between psilocybin/psilocin and CYP450 enzymes. Since the binding of drugs to CYP450 enzymes can interfere with the metabolism of other substrates leading to drug-drug interactions, this research topic is of utmost importance. Objective: This study aimed to assess potential inhibitory interactions between psilocybin/psilocin and CYP3A4, 2D6, 2B6 and 2A6. Methods: The in vitro assessment of CYP450 inhibition was performed using the Vivid®CYP450 screening kits, following the user’s guide. Concentrations of psilocybin and psilocin ranged between 1.14´10-13 - 4 mM and 6.1´10-5 - 1 mM for CYP3A4; 1.71´10-13 - 8 mM and 6.1´10-5 - 1 mM for CYP2D6; 2.4´10-4 - 8 mM and 2.4´10-5 - 1 mM for CYP2B6; and 3.8´10-6 - 2 mM and 7.6´10-8 - 1 mM for CYP2A6, respectively. Each test condition was mixed with baculosomes expressing the specific CYP, Vivid® regeneration system, NADP+, and a non-fluorescent substrate. Solvent and positive controls of inhibition, i.e., ketoconazole (CYP3A4), quinidine (CYP2D6), miconazole (CYP2B6) and tranylcypromine (CYP2A6,) were included. Fluorescence was measured for 60 minutes (Ex=415/20nm; Em=460/20nm) and the half-maximal inhibitory concentration (IC50) calculated using GraphPad prism 9.3.0. For CYP3A4 and 2D6 a minimum of three independent experiments were performed, and two independent experiments for CYP2A6 and 2B6. Results: For psilocybin, IC50 values of 49.43 mM (CYP3A4), >1000 mM (CYP2D6 and 2B6), and >300 mM (CYP2A6) were attained. For psilocin, the following IC50 values were obtained: 2.12 mM (CYP3A4), 11.89 mM (CYP2D6), 0.99 mM (CYP2A6) and 4.05 mM (CYP2B6). Conclusions: The results suggest a potential for psilocin to be an inhibitor of all the enzymes evaluated, especially CYP2A6, contrary to psilocybin which seems to only have the potential to inhibit CYP3A4.